PERIPHERAL APPLICATION OF REPETITIVE PULSE MAGNETIC STIMULATION ON JOINT CONTRACTURE FOR MOBILITY RESTORATION: CONTROLLED RANDOMIZED STUDY (International Journal of Physiotherapy, 2016)
Background: Joint contracture is a limitation in the passive or active range of motion (ROM) of a joint, where in addition to the mobility limiting factor the pain is also present. Repetitive pulsed Magnetic Stimulation (rPMS) appears to be an effective, non-invasive and safety solution for treating this condition. Therefore aim of this study was to evaluate the effect of rPMS in treating joint contracture.Methods: 30 subjects with joint contracture in the knee were enrolled in this study and divided respectively into Treatment and Control group. The treatment group were delivered with rPMS therapy. The control group was delivered with conventional physiotherapy method (ultrasound). The primary outcome measurements were: 1. Mobility evaluation by goniometry (ROM in degrees while performing flexion) and Patient Functional Assessment Questionnaire (PFAQ) for ability to perform Activities of Daily Living (ADL) and 2. Pain evaluation by 10-point Visual Analog Scale (VAS) for pain perception. Absence of adverse events was set as a secondary measure.Results: The results of the study show statistical difference (p